PROFESSIONAL DEVELOPMENT OF UNIVERSITY TEACHERS IN CONDITIONS OF UKRAINE'S INTEGRATION INTO THE EUROPEAN HIGHER EDUCATION AREA - Kirdan, Olena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The purpose of the article is to substantiate the main directions of professional development of university teachers and to ensure the excellence of teaching. The achievement of the research goal made it possible to use general theoretical methods: analysis, synthesis, specification, generalization and empirical methods: surveys and questionnaires. Results of the research. The main directions of the professional development of university teachers and ensuring the excellence of teaching are outlined: mentoring and tutoring of young teachers; creation of centers of excellence, support and development of teaching skills; development of e-learning in the centers of educational and innovative technologies etc. The experience of the Center professional development of teachers of the Pavlo Tychyna Uman State Pedagogical University is analyzed. On the basis of the conducted questionnaire of the heads of departments the peculiarities of creating a culture of support and stimulation of quality teaching, creation of an environment of professional development, promotion and recognition of best practices, etc. were established. The importance of introducing the concept of service learning pedagogy at educational programs of all levels in higher education institutions of Ukraine is emphasized; the formation of the values social responsibility of universities; policies to enhance the culture of teaching, learning and assessment.